Real time monitoring and evaluation of the inhibition effect of fucoxanthin against α-amylase activity by using QCM-A - Yin, Shipeng; Siahaan, Evi Amelia; Niu, Liqiong; Shibata, Mario; Liu, Yuanfa; Hagiwara, Tomoaki (Frontiers in Nutrition, 2023)
The main symptoms of diabetes are hyperglycemia and insulin resistance. The inhibition of the starch digestion enzymes could effectively regulate starch digestion and glucose absorption, thereby slowing or treating the symptoms of postprandial hyperglycemia. Herein, we used fucoxanthin isolated from Undaria pinnatifida stems, as α-amylase inhibitor, and monitored the interactions of both biomolecules by using QCM-A instrument. All the processes of α-amylase hydrolysis of starch were also dynamically tracked by using amylose-immobilized QCM technology. In our work, we found that the kinetic parameter (koff, kon and kcat) values obtained by the QCM-A analysis were relatively consistent compared to the kinetic parameter values obtained by the conventional Michaelis-Menten analysis. For the inhibitory reactions, the results showed that fucoxanthin significantly reduced the activity of α-amylase in a dose-dependent manner. The QCM-A technology shown to be an excellent approach in obtaining comprehensive and accurate kinetic parameters, thereby providing real and accurate data for kinetic studies. It is helpful to clarify the mechanism of action of fucoxanthin on α-amylase, which further proved the potential of fucoxanthin to improve and treat postprandial hyperglycemia.